Utility Regulators : Decisionmaking Structures, Resources, and Start-Up Strategy - Smith, Warrick (World Bank, Washington, DC, 2012)
The design of a regulatory agency's decisionmaking structure encompasses issues relating to the number of decisionmakers, the basis for selecting them, the role played by stakeholders, and the regulatory and appeals processes. The selection of the regulator is critical--especially in countries that have yet to establish a reputation for competence and reliability. When agencies are to be independent, the goal should be to select regulators with the personal qualities needed to exercise independent judgement and resist improper pressures. An appeals process is also important to ensure that the regulator does not stray from its mandate and that it remains accountable. The author outlines good practice.